Pengembangan Media Pembelajaran Interaktif dengan Lectora Inspire Materi Perakitan Komputer pada Peserta Didik SMK - Melly Novalia; Alya Andriani Putri; Noverta Effendi (Jurnal Pendidikan Teknologi Informatika dan Sains, 2019)
Normally in many schools, the media used as learning media are textbooks. Then educators explain the material with conventional methods. This can be applied to certain conditions. If done continuously without variation, it will make the students bored. Therefore, this study aims to make interactive learning media in the subject of computer assembly with Lectora Inspire. To achieve the research objectives, educational research is used with the type of Research and Development (R&D). Learning media development refers to the ADDIE model. The ADDIE stages are Analysis, Design, Development, Implementation, Evaluations. Data is collected through questionnaires (Likert scale) during the trial. Assessment results from material experts on the feasibility of interactive learning media achieved a mean score of 4.00 with a good category. The assessment results from media experts on the feasibility of interactive learning media achieved an average score of 4.65 in a very good category. Furthermore, the results of the assessment of educators on the feasibility of interactive learning media in the trial reached a mean score of 4.0 which is in a good category, while the assessment results of students on the feasibility of interactive learning media in the trial reached a mean score of 4.00 with a good category. Based on the results of the research carried out, it can be concluded that this interactive learning media is suitable to be used as an interactive learning media for computer assembly subject. Keywords Interactive Learning Media, Computer Assembly, Lectora Inspire.